Strategi Pemasaran Dalam Upaya Meningkatkan Jumlah Nasabah Simpan Pinjam Di KSP Hardana - Anas Zaki Hino Putra; Yunita Fitri W (Jurnal Manajemen DIVERSIFIKASI, 2025)
In this study, we will explore the diverse strategies employed by the Hardana Cooperative. Our primary aim is to uncover various internal and external factors influencing the Cooperative. By gaining a deeper understanding of these elements, we hope to develop a marketing strategy that is both relevant and aligned with the Cooperative's objectives. This research employs a qualitative approach, utilizing a variety of data collection techniques, including interviews with the Supervisor of the Hardana Cooperative, field observations, and analysis of relevant documentation. The collected data will be analyzed using the SWOT method. We anticipate that the findings from this study will yield a range of effective marketing strategies for the Hardana Cooperative. Through a comprehensive analysis of the business environment, we aim to identify opportunities that will allow the Cooperative to expand and enhance its operations.